Causal association between air pollution and frailty: a Mendelian randomization study - Haixia Xiao; Shan Huang; Wei Yang; Wenni Zhang; Huanshun Xiao; Shuangming Cai (Frontiers Media S.A., 2023)
BackgroundsFrailty is a significant problem for older persons since it is linked to a number of unfavorable consequences. According to observational researches, air pollution may raise the risk of frailty. We investigated the causal association between frailty and air pollution (including PM2.5, PM2.5-10, PM10, nitrogen dioxide, and nitrogen oxides) using Mendelian randomization approach.MethodsWe conducted MR analysis using extensive publically accessible GWAS (genome-wide association studies) summary data. The inverse variance weighted (IVW) method was employed as the primary analysis method. The weighted median model, MR-Egger, simple model, and weighted model approaches were chosen for quality control. The Cochran's Q test was utilized to evaluate heterogeneity. Pleiotropy is found using the MR-Egger regression test. The MR-PRESSO method was used to recognize outliers. The leave-one-out strategy was used to conduct the sensitivity analysis.ResultsMR results suggested that PM2.5 was statistically significantly associated with frailty [odds ratio (OR) = 1.33; 95%confidence interval (CI) = 1.12-1.58, p = 0.001] in IVW method. We observed no statistical association between PM2.5-10(OR = 1.00, 95% CI = 0.79-1.28, p = 0.979), PM10(OR = 0.91, 95% CI = 0.75-1.11, p = 0.364), nitrogen dioxide (OR = 0.98, 95% CI = 0.85-1.12, p = 0.730), nitrogen oxides (OR = 1.15, 95% CI = 0.98-1.36, p = 0.086) and frailty. There was no pleiotropy in the results. The sensitivity analysis based on the leave-one-out method showed that the individual single nucleotide polymorphisms (SNPs) did not affect the robustness of the results.ConclusionThe current MR investigation shows a causal association between PM2.5 and frailty. Frailty's detrimental progression may be slowed down with the help of air pollution prevention and control.